The Effect of UV Irradiation to a-C:H on Friction and Wear Properties under PAO Oil Lubrication Including MoDTC and ZnDTP - Mohd Taufik bin Taib (Japanese Society of Tribologists, 2018)
One of the solutions to reduce friction between two sliding surfaces in automobile engine is by applying DLC coating to engine components. However, it is critical that the effect of lubricant additives to DLC coating to be clarified before hands as to avoid components failure. In this study, tribological friction test between SUJ2 balls and as-deposited plus UV irradiated a-C:H coatings was conducted to clarify the effect of ultraviolet irradiation to DLC coating in four different additives added lubricant oils. AFM, nano-indentation hardness test, ellipsometery, Zygo, and EDS-SEM were used to investigate the effect of UV irradiation to a-C:H DLC before and after friction test. Prior the friction test, the results showed that UV irradiation presented no significant change in terms of hardness and roughness but the irradiation did penetrate into topmost surface of the a-C:H coating to several degree and created dangling bonds available to interact with lubricant additives elements. Friction test results showed that UV irradiated a-C:H coatings presented lower friction coefficient than as deposited a-C:H coatings. Worn surface analysis revealed that UV irradiated a-C:H coatings attracted more lubricant additives element to attach on its surface thus created thicker tribofilm on its own surface and its counter materials, resulted in lower friction coefficient than the as-deposited a-C:H coatings.